The morphological evolution of the Adephaga (Coleoptera). (5th December 2019) - Beutel, Rolf Georg; Ribera, Ignacio; Fikáček, Martin; Vasilikopoulos, Alexandros; Misof, Bernhard; Balke, Michael
Abstract: The evolution of the coleopteran suborder Adephaga is discussed based on a robust phylogenetic background. Analyses of morphological characters yield results nearly identical to recent molecular phylogenies, with the highly specialized Gyrinidae placed as sister to the remaining families, which form two large, reciprocally monophyletic subunits, the aquatic Haliplidae + Dytiscoidea (Meruidae, Noteridae, Aspidytidae, Amphizoidae, Hygrobiidae, Dytiscidae) on one hand, and the terrestrial Geadephaga (Trachypachidae + Carabidae) on the other. The ancestral habitat of Adephaga, either terrestrial or aquatic, remains ambiguous. The former option would imply two or three independent invasions of aquatic habitats, with very different structural adaptations in larvae of Gyrinidae, Haliplidae and Dytiscoidea. Abstract : This study presents the largest set of morphological characters of adults and immature stages ever compiled for the coleopteran suborder Adephaga. Analyses of the morphological characters yield results nearly identical to recent analyses of molecular data, suggesting that a stable phylogeny has been achieved. The character transformation on the phenotypic level is reconstructed using a formal approach for the first time, based on the robust phylogenetic pattern and mesquite .